The Role of Forensic Accounting in Reducing the Practice of Earning Management in Libyan Commercial Banks - عبد القادر العريبي, خالد; عوض نجم, آية (Dirasat in Economics and Business, 2024)
The purpose of the study to know the role of forensic accounting in reducing the practice of earnings management in Libyan commercial banks. The study employed a descriptive analytical approach to meet its goals, and the questionnaire served as a research instrument to survey a sample of 213 individuals —including financial experts from the courts, financial bank managers, academic staff in accounting department, auditors from the Audit Bureau, and external auditors have registered with Libyan central bank. The study hypothesis was tested, namely: the main hypothesis (there is a role for forensic accounting in limiting the practice of earnings management in Libyan commercial banks), and four sub-hypothesis branches out from the main hypothesis. The study concluded that there is a role for forensic accounting in reducing the practice of earning management in Libyan commercial banks. The study also, showed that using forensic accounting procedures and techniques can help present financial statements in a fair and impartial manner, that the forensic accountant presents his opinion to the judiciary as a financial expert on financial issues, and that the phenomenon of earnings management has affected many banks through the quality of the financial statements issued by them. The study recommended that it be applied in the banking environment, that forensic accounting be included in university curricula, and that previous countries' experiences be leveraged, because forensic accounting has proven to be effective in decreasing the practice of earning management in Libyan commercial banks.